(untitled) (Journal of Oriental Studies, 2025)
The research paper reviewed and analyzed research in Japanese and English on the topic of cross-border marriage migration. The subject of the study is the research materials on marriage migration in Japan. The purpose of the research work is to determine the level of study of marriage migration. The objectives of the work are to collect, systematize works written in this field, consider trends in research topics considered in this field, identify development trends, identify scientists contributing to this field, review their work, and analyze the specifics of each researcher’s work. The relevance of the research is that the works in Japanese and English, which studied the issue of international marriage from established history, differ from each other and separately dwell on chronological and geographical features. As a result, it was concluded that depending on the countries of arrival of marriage migrants, the reasons, the social and economic situation in the Japanese country, the goals, interests of marriage migrants, their perception by society, the scope of research conducted by scientists, research work, topics, and trends were different, in connection with which the research work was classified by country, region, cultural, national characteristics of each country, and economic and social development of the country by years, increasing the value of this research work and becoming more practical relevance. Keywords: Cross-border marriage, marriage migration, migration, demography